Are corporate social responsibility (CSR) initiatives such as sustainable development and environmental policies value enhancing or window dressing?. (17th April 2018) - Taylor, Joseph; Vithayathil, Joseph; Yim, Dobin
Abstract: The natural‐resource‐based view of the firm suggests that there are benefits associated with voluntary disclosure of its corporate social responsibility (CSR) activities, in that this signals quality of management, as well as the quality of the firm's financial strategy, to its investors. With increased demand for transparency of firm activities, this assertion needs re‐examination. We examine the effects of governance, environmental and social responsibility performance on the firm, and find moderate support for CSR disclosure increasing firm value. However, only the disclosure of social responsibility scores was associated with higher levels of firm value, as measured by Tobin's q . This relationship was positively moderated by the extent to which a firm was consumer facing. These findings suggest that strategic engagement in social responsibility, rather than merely sponsoring environmental initiatives, contributes to increasing firm value through CSR.